2017
DOI: 10.18410/jebmh/2017/529
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Its Risk Factors- A Cross Sectional Study in Rural Area

Abstract: BACKGROUND An elevated arterial pressure is probably the most important public health problem in developing & developed countries. Hypertension is the commonest cardiovascular disorder and one of the major risk factor for cardiovascular mortality. MATERIALS AND METHODS The present study was conducted in rural field practice area of the Department of Community medicine Katihar Medical College, Katihar. A sample of 500 families was selected by systematic sampling technique from all the families registered at Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Genetic factors contributed to the occurrence of hypertension around 30-60% in various individuals (Singh, 2017). Hereditary factors played a role in the occurrence of hypertension compared to environmental factors.…”
Section: The Effect Of History Of Hypertension On Hypertensionmentioning
confidence: 99%
“…Genetic factors contributed to the occurrence of hypertension around 30-60% in various individuals (Singh, 2017). Hereditary factors played a role in the occurrence of hypertension compared to environmental factors.…”
Section: The Effect Of History Of Hypertension On Hypertensionmentioning
confidence: 99%
“…Kurang aktifitas fisik meningkatkan kejadian hipertensi [8] dan secara signifikan aktifitas fisik terkait dengan penurunan resiko hipertensi [9]. Prevalensi hipertensi tinggi pada subjek yang memiliki aktifitas fisik rendah [10]. Aktifitas fisik secara teratur dapat mencegah hipertensi [11].…”
Section: Pembahasanunclassified
“…The previous researches have revealed that approximaltly up to 50% of obese adolescents remain obese in adulthood (Calle, Rodriguez, Walker-Thurmond, & Thun, 2003;Flegal et al, 2013;Krause, Ware, McPherson, Lennox, & O'Callaghan, 2016). In addition to the increased potential risks for health problems, adolescents still face immediate health consequences due to obesity, including hyperlipidemia (Rao et al, 2016), hypertension (Singh, Pandey, & Rani, 2017) and other physiological and psychological problems (Crews, Schneider, Yalla, Reeves, & Vileikyte, 2016). In addition, previous researches have shown high levels of dissatisfaction with body size and shape amongst femal colledge students, as well as a desire to be thinner with trend of more prevalent among girls (Joseph et al, 2016;Moussally, Brosch, & Van der Linden, 2016), and other psychological issues of low self esteem, depression, et al (Crews et al, 2016).…”
Section: Introductionmentioning
confidence: 99%